SATU GENERASI, TETAPI BERBEDA VISI: PERSEPSI CINTA MENURUT SAFITRI DAN DIKA ONE GENERATION, BUT A DIFFERENT VISION: PERCEPTION OF LOVE ACCORDING SAFITRI AND DIKA - Saksono - Prijanto (Universitas Nasional, 2015)
ABSTRACT Product types literary readings also increasingly spectacular. They now deliver